What’s in a price? the American raw cotton market in Liverpool and the Anglo-American war - Haggerty, Sheryllynne (Taylor and Francis, 2018)
This article argues that an embryonic futures market was present in Liverpool during the Anglo-American war. The analysis of a previously unseen dataset of printed Prices Currents has facilitated not only a price series of raw cotton prices, but an in-depth analysis of the ‘construction’ of those raw cotton prices. By positing a definition of.an embryonic futures market and then analysing each of the features of a such a market in turn, this study demonstrates the existence of an embryonic futures market in early nineteenth-century Liverpool.